Matrix metalloproteinases and their inhibitors - O. S. Grigorkevich; G. V. Mokrov; L. Yu. Kosova (LLC "Publisher OKI", 2019)
Metalloproteinase was discovered by Gross and Lapierre in 1962 for the first time. Since then, more than 20 enzymes of this family have been characterized, and their functions have been studied in detail. Metalloproteinases take part in blood pressure regulation, the cell matrix extension and remodeling, anesthesia, multiple sclerosis, blood coagulation, wound healing, tumor transformation and metastasis, etc. This review covers structure of matrix metalloproteinases, their mechanism of action, as well as MMP's endogenous and exogenous inhibitors. A special place is occupied by analysis of approaches to matrix metalloproteinases synthetic inhibitors and their activity. This review demonstrates the perspectivity of new selective matrix metalloproteinase inhibitors design.